MULTI-RESOLUTION IN REMOTE SENSING FOR AGRICULTURAL MONITORING: A REVIEW - Zullo Junior, Jurandir; Coltri, Priscila Pereira; Gonçalves, Renata Ribeiro do Valle; Romani, Luciana Alvim Santos (Revista Brasileira de Cartografia, 2014)
We present a review of literature on remote sensing spatial and temporal images resolution applied to agriculture purposes. In this paper, the defi nitions are reviewed and a focus is given on the applications of resolutions in agricultural studies. A few main applications with low, medium and high spatial resolution focus were selected for this review, especially in sugarcane and coffee crops, where remote sensing contributions are traditionally important. The paper starts with an overview of agriculture and remote sensing, focused on the history of spatial and temporal resolutions uses. This section is followed by a review of low spatial and high temporal resolution systems, with important results in sugarcane. In this section studies conclude that sensors like AVHRR/NOAA can significantly contribute to improve sugarcane monitoring, as well as help understanding of development and expansion. After that, we present medium and high spatial resolution systems, especially for coffee crops that have been showing good results in fi ne scale, with detailed information. Studies conclude that satellites like Geoeye and IKONOS can obtain biophysical information of the culture and satellites like Landsat can monitor the coffee growing. Finally the review presents a conclusion with some key recommendations.